6.4.13 5.1

   6.4.13.1 [1103] Problem 1
   6.4.13.2 [1104] Problem 2
   6.4.13.3 [1105] Problem 3
   6.4.13.4 [1106] Problem 4
   6.4.13.5 [1107] Problem 5
   6.4.13.6 [1108] Problem 6

6.4.13.1 [1103] Problem 1

problem number 1103

Added Feb. 25, 2019.

Problem Chapter 4.5.1.1, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\) \[ a w_x + b w_y = c \ln (\lambda x + \beta y) w \]

Mathematica

\[\left \{\left \{w(x,y)\to c_1\left (y-\frac{b x}{a}\right ) \exp \left (\frac{c \left (\frac{(a \beta y-b \beta x) \log (a (\beta y+\lambda x))}{a \lambda +b \beta }+x \log (\beta y+\lambda x)-x\right )}{a}\right )\right \}\right \}\]

Maple

\[w \left ( x,y \right ) = \left ( \beta \,y+\lambda \,x \right ) ^{{\frac{c \left ( \beta \,y+\lambda \,x \right ) }{a\lambda +b\beta }}}{\it \_F1} \left ({\frac{ya-bx}{a}} \right ){{\rm e}^{-{\frac{c \left ( \beta \,y+\lambda \,x \right ) }{a\lambda +b\beta }}}}\]

________________________________________________________________________________________

6.4.13.2 [1104] Problem 2

problem number 1104

Added Feb. 25, 2019.

Problem Chapter 4.5.1.2, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a w_x + b w_y = \left ( c \ln (\lambda x)+ k \ln (\beta y) \right ) w \]

Mathematica

\[\left \{\left \{w(x,y)\to e^{-\frac{x (c+k)}{a}} (\lambda x)^{\frac{c x}{a}} (\beta y)^{\frac{k y}{b}} c_1\left (y-\frac{b x}{a}\right )\right \}\right \}\]

Maple

\[w \left ( x,y \right ) = \left ( \lambda \,x \right ) ^{{\frac{cx}{a}}} \left ( \beta \,y \right ) ^{{\frac{ky}{b}}}{\it \_F1} \left ({\frac{ya-bx}{a}} \right ){{\rm e}^{{\frac{-aky-cxb}{ab}}}}\]

________________________________________________________________________________________

6.4.13.3 [1105] Problem 3

problem number 1105

Added Feb. 25, 2019.

Problem Chapter 4.5.1.3, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a w_x + b \ln ^n(\lambda x) w_y = \left ( c \ln ^m(\mu x)+ s \ln ^k(\beta y) \right ) w \]

Mathematica

\[\left \{\left \{w(x,y)\to c_1\left (y-\frac{b (-\log (\lambda x))^{-n} \log ^n(\lambda x) \text{Gamma}(n+1,-\log (\lambda x))}{a \lambda }\right ) \exp \left (\int _1^x\frac{s \log ^k\left (\frac{\beta \left (-b \text{Gamma}(n+1,-\log (\lambda x)) \log ^n(\lambda x) (-\log (\lambda x))^{-n}+b \text{Gamma}(n+1,-\log (\lambda K[1])) (-\log (\lambda K[1]))^{-n} \log ^n(\lambda K[1])+a \lambda y\right )}{a \lambda }\right )+c \log ^m(\lambda K[1])}{a}dK[1]\right )\right \}\right \}\]

Maple

\[w \left ( x,y \right ) ={\it \_F1} \left ( -\int \!{\frac{b \left ( \ln \left ( \lambda \,x \right ) \right ) ^{n}}{a}}\,{\rm d}x+y \right ){{\rm e}^{\int ^{x}\!{\frac{1}{a} \left ( c \left ( \ln \left ({\it \_b}\,\lambda \right ) \right ) ^{m}+s \left ( \ln \left ( \beta \, \left ( \int \!{\frac{b \left ( \ln \left ({\it \_b}\,\lambda \right ) \right ) ^{n}}{a}}\,{\rm d}{\it \_b}-\int \!{\frac{b \left ( \ln \left ( \lambda \,x \right ) \right ) ^{n}}{a}}\,{\rm d}x+y \right ) \right ) \right ) ^{k} \right ) }{d{\it \_b}}}}\]

________________________________________________________________________________________

6.4.13.4 [1106] Problem 4

problem number 1106

Added Feb. 25, 2019.

Problem Chapter 4.5.1.4, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a w_x + b \ln ^n(\lambda y) w_y = \left ( c \ln ^m(\mu x)+ s \ln ^k(\beta y) \right ) w \]

Mathematica

\[\left \{\left \{w(x,y)\to c_1\left (\frac{(-\log (\lambda y))^n \log ^{-n}(\lambda y) \text{Gamma}(1-n,-\log (\lambda y))}{\lambda }-\frac{b x}{a}\right ) \exp \left (\int _1^y\frac{\log ^{-n}(\lambda K[1]) \left (s \log ^k(\beta K[1])+c \log ^m\left (\frac{-a \text{Gamma}(1-n,-\log (\lambda y)) (-\log (\lambda y))^n \log ^{-n}(\lambda y)+a \text{Gamma}(1-n,-\log (\lambda K[1])) (-\log (\lambda K[1]))^n \log ^{-n}(\lambda K[1])+b \lambda x}{b}\right )\right )}{b}dK[1]\right )\right \}\right \}\]

Maple

\[w \left ( x,y \right ) ={\it \_F1} \left ( -{\frac{a\int \! \left ( \ln \left ( y\lambda \right ) \right ) ^{-n}\,{\rm d}y}{b}}+x \right ){{\rm e}^{\int ^{y}\!{\frac{ \left ( \ln \left ({\it \_b}\,\lambda \right ) \right ) ^{-n}}{b} \left ( c \left ( \ln \left ( \lambda \, \left ( \int \!{\frac{ \left ( \ln \left ({\it \_b}\,\lambda \right ) \right ) ^{-n}a}{b}}\,{\rm d}{\it \_b}-{\frac{a\int \! \left ( \ln \left ( y\lambda \right ) \right ) ^{-n}\,{\rm d}y}{b}}+x \right ) \right ) \right ) ^{m}+s \left ( \ln \left ( \beta \,{\it \_b} \right ) \right ) ^{k} \right ) }{d{\it \_b}}}}\]

________________________________________________________________________________________

6.4.13.5 [1107] Problem 5

problem number 1107

Added Feb. 25, 2019.

Problem Chapter 4.5.1.5, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ \ln (\beta y) w_x + a \ln (\lambda x) w_y = b w \ln (\beta y) \]

Mathematica

\[\left \{\left \{w(x,y)\to e^{b x} c_1\left (y \left (\log \left (\beta y e^{\frac{a x}{y}} x^{-\frac{a x}{y}} \lambda ^{-\frac{a x}{y}}\right )-1\right )\right )\right \}\right \}\]

Maple

\[w \left ( x,y \right ) ={\it \_F1} \left ({\frac{-\ln \left ( \lambda \,x \right ) xa+ax+\ln \left ( \beta \,y \right ) y-y}{a}} \right ){{\rm e}^{bx}}\]

________________________________________________________________________________________

6.4.13.6 [1108] Problem 6

problem number 1108

Added Feb. 25, 2019.

Problem Chapter 4.5.1.6, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a \ln (\lambda x)^n w_x + b \ln (\beta y)^k w_y = c \ln (\gamma x)^m w \]

Mathematica

Failed

Maple

\[w \left ( x,y \right ) ={\it \_F1} \left ( -\int \! \left ( \ln \left ( \lambda \,x \right ) \right ) ^{-n}\,{\rm d}x+\int \!{\frac{ \left ( \ln \left ( \beta \,y \right ) \right ) ^{-k}a}{b}}\,{\rm d}y \right ){{\rm e}^{\int \!{\frac{c \left ( -3\,\ln \left ( 2 \right ) +\ln \left ( x \right ) \right ) ^{m} \left ( \ln \left ( \lambda \,x \right ) \right ) ^{-n}}{a}}\,{\rm d}x}}\]

________________________________________________________________________________________